Preferences of Medical Sciences Students for Work Contracts in Deprived Areas of Iran: A Discrete Choice Experiment Analysis [Erratum] - Kazemi Karyani A; Karami Matin B; Malekian P; Moradi Rotvandi D; Amini S; Delavari S; Soltani S; Rezaei S (Dove Medical Press, 2021)
Kazemi Karyani A, Karami Matin B, Malekian P, et al. Risk Manag Healthc Policy. 2020;13:927–939. The authors have advised that there is an error in Table 3 of the published paper which was introduced by the Editorial staff during the publication process. Page 935, Table 3, Major, Medicine, aOR column, Workload (base: low), Moderate row the value “41.15” should read “1.15”. Read the original article